Mathematical modelling of a refinery furnace - Burhanoğlu, Yüksel. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1985., 1985)
In this study, a mathematical model for the multiple fuel fired, Born type refinery furnace is derived in order to find temperature distribution in the furnace and vapor fraction of the charge. The model is solved by the numerical methods using computer programs written by the author. The model is available for steady-state. The necessary parameters such as air flowrate, molecular weight of flue gas, flue gas flowrate and adiabatic flame temperature which are not present in the data are calculated by material and energy balances. The furnace is analyzed in two sections with the assumption of one-dimensional heat transfer for gas and charge. The sections are defined according to the dominating heat transfer mechanism from the heat source, which are radiation and convection sections. Radiation section is further divided into three parts according to type of flow' of charge and location of tubes in which charge flows that are: (1) single phase flow in tubes on the walls, (2) two phase flow in tubes on the walls, (3) two phase flow in tubes at the ceiling of the radiation section. Both sections are divided into stages corresponding to each row of tubes. Temperature distribution in the furnace is found by making energy balances in each stage of each section. Vapor fraction of change at each stage is evaluated also by energy balances in two phase region. On the basis of modelling equations a computer program is developed for the furnace which uses an iterative procedure. Besides obtaining the numerical solutions of the model, the effect of change in input parameters on output conditions are also evaluated.
Keywords: Furnaces.; Mathematical models.